Implementasi Program Baca Tulis AL-Qur’an (BTQ) - Titin Mariatul Qiptiyah; Reni Soflianti (TASAMUH: Jurnal Studi Islam, 2021)
The teacher is a strategic factor in education, responsible for the success of the development of students with all cognitive, affective, and psychomotor potential. The teacher is responsible for the learning process at the institution where he is assigned, because the system applied by the teacher affects the quality of learning completeness. Therefore, teachers must improve their knowledge and intellect and strive to be good role models for their students. Teachers are also required to advance their students' abilities in the field of science as well as in the field of morality. This study raises the general problem, how is the role of the teacher in the implementation of learning to read and write the Qur'an at Madrasah Aliyah Roudlotul Mutaallim Baratan, Patrang District, Jember Regency. This research uses phenomenological qualitative research. The results of the study indicate that in general the teacher's role in the implementation of learning to read and write the Qur'an is to act as a teacher and act as a mentor, in general the results can improve the quality of students. As evidence is the result of research conducted by the author of Madrasah Aliyah Roudlotul Mutaallim Baratan, Patrang District, Jember Regency